การศึกษาสมรรถนะด้านเทคโนโลยีสารสนเทศเพื่อเข้าสู่ AEC ของผู้บริหาร ของโรงเรียนมัธยมศึกษาขนาดใหญ่จังหวัดเพชรบุรี - พลอยทับทิม พชระ; เจริญกุล นันทรัตน์ (An Online Journal of Education, 2018)
The purposes of the research were to study and compare administrators and teachers’ opinions about the administrators information technology competencies towards Asean Economics Community. The conceptual framework of this research was based on information technology competencies of administrators in knowledge, skills and attitudes. The sample population consisted of 33 administrators and 246 teachers from 8 large secondary schools in Phetchaburi Province. The research instrument used in this study was a questionnaire. The data were analyzed using frequency distributes, percentage, mean ( x ),standard deviation and t-test. The research findings revealed that Information technology competencies of administrators were at a high level both overall and in each aspect, ranking from the highest to the lowest : attitudes, skills and knowledge capacity. The opinions of administrators and teachers were different at a significant level of .05.